Capillary imbibition in mortars with natural pozzolan, limestone powder and slag evaluated through neutron radiography, electrical conductivity, and gravimetric analysis. (April 2019) - Alderete, N.; Villagrán Zaccardi, Y.; Snoeck, D.; Van Belleghem, B.; Van den Heede, P.; Van Tittelboom, K.; De Belie, N.
Abstract: The description of the capillary imbibition phenomenon can help to understand and enhance the durability of cementitious materials containing supplementary cementitious materials (SCMs). We studied the effect of slag, natural pozzolan and limestone powder on mortars by means of gravimetric analysis, electrical conductivity and neutron radiography during capillary imbibition. From the conductivity and water uptake results, the dominant dilution effect of limestone powder was revealed whereas refinement of the pore structure was obtained when using slag or natural pozzolan. Results from gravimetric analysis showed a good correspondence with the recently proposed fourth root of time approach. Calculations based on the neutron radiographs showed that the main water flow also advances with the fourth root of time. This gives support to the hypothesis of variable hydraulic diffusivity in cementitious materials. Furthermore, during the first 6 h, the water front did not follow the sharp front model that is usually assumed.